Analysis of Integrated Quality Management Implementation Failure: A Systematic Literature Review in the Context of Education and Public Services - Yuvita Rahayu; Vica Ris Namira Putri Herdianto; Karunia Nafisah; Mualimin Mualimin (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
Total Quality Management (TQM) has become an i mportant approach to improving organizational performance through continuous improvement efforts. However, various studies show that its implementation often fails due to structural and cultural constraints within the organization. This makes a critical review of the causes of failure and success factors of TQM important to conduct as a basis for developing sustainable quality practices. This literature review article aims to analyze the factors causing the failure of TQM implementation and map related research trends, by answering two research questions: (1) What factors influence the success or failure of TQM implementation according to previous research? (2) What research gaps remain unanswered in TQM studies? The method used is a systematic literature review by searching articles through Google Scholar and DOAJ using the keywords TQM, TQM, quality implementation, and organizational quality. Of the 18 initial articles, 6 relevant articles were analyzed thematically. The review results indicate three main themes: the importance of leadership in quality management, the challenges of organizational culture to the success of TQM, and the impact of TQM implementation on organizational performance. Previous studies have been limited to descriptive studies and the context of education and public services. Therefore, future research needs to develop context-based MMT implementation models, strengthen empirical approaches, and integrate modern management innovations.